Synthesis of Palladium Nanoparticles by the Thermal Destruction of Pd(II) Solvate Complexes in Alcohols - Buryak, N.I.; Volkov, S.V. (Наносистеми, наноматеріали, нанотехнології, 2008)
The composition and structure of Pd(II) solvate complexes in alcohols within
the temperature range of 20—150°C are investigated by spectroscopic methods. Досліджено спектроскопічними методами склад та будову сольватокомплексів Pd(II) в спиртах в інтервалі температур 20—150°С. Исследованы спектроскопическими методами состав и строение сольватокомплексов Pd(II) в спиртах при температуре 20—150°С.